2021
DOI: 10.3390/foods10081932
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profile, Antioxidative and Antihyperglycemic Properties of Padina tetrastromatica from Tioman Island, Malaysia

Abstract: Seaweeds are an important ingredient of functional foods recommended for daily food, due to their unique compositions and nutritional value. Padina tetrastromatica is a brown edible seaweed that is commonly found along the coastal regions of Peninsular Malaysia and consumed as food by some coastal communities. This study investigates the nutritional and antihyperglycaemic potential of P. tetrastromatica extracts, which is generally accepted as an important functional food. In our methodology, we induced diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
2
5
1
Order By: Relevance
“…The protein content of the three studied species ranged from 8.30 ± 0.37 % ( P. tetrastromatica ) to 30.63 ± 0.90 % ( G. longissima ) of DW and significantly higher (P < 0.05) amount of protein was found in G. longissima ( Table 1 ). The current findings were similar to the findings of Jannat-Alipour et al [ 26 ]; Rosemary et al [ 18 ]; Palaniveloo et al [ 11 ]. The content of protein in seaweeds are generally higher in red seaweeds than the brown and green seaweeds [ 8 , 27 ] which supports our current findings.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The protein content of the three studied species ranged from 8.30 ± 0.37 % ( P. tetrastromatica ) to 30.63 ± 0.90 % ( G. longissima ) of DW and significantly higher (P < 0.05) amount of protein was found in G. longissima ( Table 1 ). The current findings were similar to the findings of Jannat-Alipour et al [ 26 ]; Rosemary et al [ 18 ]; Palaniveloo et al [ 11 ]. The content of protein in seaweeds are generally higher in red seaweeds than the brown and green seaweeds [ 8 , 27 ] which supports our current findings.…”
Section: Resultssupporting
confidence: 92%
“…This is because the ratio of sodium (Na) to potassium (K) in this product is less than 1, which aligns with the recommended dietary choices for individuals with high blood pressure [ 32 ]. Additionally, seaweeds with low Na/K ratios are good for replacing sodium chloride [ 11 ]. According to seaweed species, location, wave, season, environment, physiological parameters, processing type, and mineralization technique, mineral concentrations might differ [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Armas et al [24] reported that the carbohydrate content of Padina pavonica (43,39%), Sargassum (40.04%) and Ulva lactuca (45.32%) was higher than in this study. Whereas previous study reported that crude carbohydrate of Sargassum hystrix (31.53%) [21], Ulva (16.63%) [26] and Padina (23.16%) [27]. Differences in carbohydrate content are determined by water quality conditions [28].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the present study demonstrated a comparative study between the chemically synthesized silver nanoparticles with green synthesized silver nanoparticles (using P. tetrastromatica) and estimated their possible role in controlling melanoma cancer both in in vitro and in vivo mice models. , To perform a risk assessment of these two types of silver nanoparticles, the genotoxicological profile was also determined. , The overall study demonstrates the first ever comparison of both therapeutic efficacies and genotoxicological profiles of these two silver nanoparticles (green and chemical synthesized) in both in vitro and in vivo models that are very much essential before their clinical use.…”
Section: Introductionmentioning
confidence: 89%